Gorontalo People's Interest in Local Wisdom of Dikil Culture - Misran Rahman; Endah Setiyowati; Yakob Napu; Zulkarnain Anu (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
The cultural tradition of "dikili" is a culture of local wisdom of the Gorontalo tribe that has been carried out by the people of Gorontalo for generations in commemoration of the Birthday of the Prophet Muhammad SAW. However, today the existence of this culture is less attractive to the public to learn it. Therefore, the purpose of this study is to provide an overview of the interest analysis in question while trying to provide several scientific solutions.The method used in this study is descriptive with a qualitative approach. Research techniques are interview, observation, and document study techniques.The results showed that the community still has a considerable interest in organizing dikili culture. Similarly, officers are still represented to have a high enough interest to carry out their duties. However, public interest in learning to be represented and become officers is still low.